2018
DOI: 10.1186/s12878-018-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic state augmented with platelet indices among Sudanese diabetic septic foot

Abstract: BackgroundDiabetes mellitus is a very rampant metabolic disorder, particularly type II. It has many complications such as the septic foot. Diabetic septic foot (DSF) patients are at high risk for coagulation abnormalities as well as surgical hazards. Owing to the potential sequelae of coagulation and vascular abnormalities, this work aimed at studying the hemostatic state and platelet indices in diabetes type II patients with septic foot.MethodsA case-control study was conducted during the period from July to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
0
9
0
1
Order By: Relevance
“…38 Bashir's study indicated that APTT value was significant in diabetic septic foot patients compared to non-diabetic septic foot patients (32.64 ± 5.2 versus 28.49 ± 4.13, p < 0.01), and the author held that APTT was associated with prothrombotic state and hypercoagulability in patients with diabetic septic foot. 39 Some diseases that may prolong APTT value, such as liver disease, vitamin K deficiency, sepsis, and disseminated intravascular coagulation and so on, were not found in the case data. We did the correlation test between APTT and other variables, and the results showed that WBC, Hb, ALB were correlated with APTT, which was statistically significant as shown in the figure below, but the correlation was slight (r = 0.155, r = 0.252, r = 0.247).…”
Section: Discussionmentioning
confidence: 81%
“…38 Bashir's study indicated that APTT value was significant in diabetic septic foot patients compared to non-diabetic septic foot patients (32.64 ± 5.2 versus 28.49 ± 4.13, p < 0.01), and the author held that APTT was associated with prothrombotic state and hypercoagulability in patients with diabetic septic foot. 39 Some diseases that may prolong APTT value, such as liver disease, vitamin K deficiency, sepsis, and disseminated intravascular coagulation and so on, were not found in the case data. We did the correlation test between APTT and other variables, and the results showed that WBC, Hb, ALB were correlated with APTT, which was statistically significant as shown in the figure below, but the correlation was slight (r = 0.155, r = 0.252, r = 0.247).…”
Section: Discussionmentioning
confidence: 81%
“…30 Impairment of coagulation, fibrinolysis and platelet function increases the risks of thrombogenesis, atherosclerosis progression and plaque formation. 20,31 In this study, type 2 DM patients were at higher risk of DF than type 1 DM patients. This is in line with clinical studies showing a high susceptibility of type 2 DM patients to DF.…”
Section: Discussionmentioning
confidence: 59%
“…Beberapa penelitian melaporkan adanya insignifiknasi pada FVIII antara DMT2 dengan individu normal yang sehat. Peningkatan FVIII lebih biasanya disertai pula dengan peningkatan konsentrasi VWF (Bashir and Ali, 2018).…”
Section: Pendahuluanunclassified